2019
DOI: 10.1093/jas/skz258.852
|View full text |Cite
|
Sign up to set email alerts
|

PSXII-42 The lactational response in dairy cows to supplementation of calcium gluconate embedded in a fat matrix

Abstract: Functional nutrients that facilitate gastrointestinal health may serve as an alternative to the use of antimicrobials in animal production systems. Gluconic acid has been used as a prebiotic health promoter in non-ruminant applications. It is poorly absorbed in the small intestine and is fermented to butyrate in the lower gastrointestinal tract. The gut health benefits of butyrate have been demonstrated in both non-ruminant and ruminant models, but effects of post-ruminal gluconic acid supplementation are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…McKnight et al (2019) observed differential responses between feeding unprotected calcium gluconate and post-ruminal delivery of the same compound, highlighting the need for calcium gluconate to circumvent extensive fermentation in the rumen. Given the production responses in multiparous animals in this study and other studies with the same HFCG supplement (Doelman et al, 2019a, Seymour et al, 2021b are similar to those observed with post-ruminal infusion of calcium gluconate (Doelman et al, 2019b, McKnight et al, 2019, this suggests that the fat matrix of the HFCG supplement is able to provide protection from the rumen environment to allow a sufficient amount of calcium gluconate to reach the lower parts of the digestive tract intact. Dietary butyrate has been implicated in improvements in gut health and epithelial integrity, as well as in responses in whole body lipid and energy metabolism (as reviewed by den Besten et al, 2013, Liu et al, 2018.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…McKnight et al (2019) observed differential responses between feeding unprotected calcium gluconate and post-ruminal delivery of the same compound, highlighting the need for calcium gluconate to circumvent extensive fermentation in the rumen. Given the production responses in multiparous animals in this study and other studies with the same HFCG supplement (Doelman et al, 2019a, Seymour et al, 2021b are similar to those observed with post-ruminal infusion of calcium gluconate (Doelman et al, 2019b, McKnight et al, 2019, this suggests that the fat matrix of the HFCG supplement is able to provide protection from the rumen environment to allow a sufficient amount of calcium gluconate to reach the lower parts of the digestive tract intact. Dietary butyrate has been implicated in improvements in gut health and epithelial integrity, as well as in responses in whole body lipid and energy metabolism (as reviewed by den Besten et al, 2013, Liu et al, 2018.…”
Section: Discussionsupporting
confidence: 82%
“…Animals assigned to the HFCG treatment were offered a TMR (Table 1) with the HFCG supplement (Trouw Nutrition, Amersfoort, the Netherlands). The supplement was composed of 50% hydrogenated palm fat, 40% calcium gluconate and 10% calcium carbonate, and was included at a rate of 4.3 kg/tonne in the dry period compound feed and 1.37 kg/tonne in the lactation compound feed, to achieve a targeted intake of the HFCG product of approximately 16 g/d based on a previous pilot study (Doelman et al, 2019a). Animals assigned to the CON treatment were offered the same basal TMRs without the supplement.…”
Section: Methodsmentioning
confidence: 99%
“…The observed production responses could be explained in part by an increase in production of VFA by hindgut microbes in response to HFCG supplementation, although we observed no difference in fecal acetate, propionate, or butyrate concentrations. This agrees with Doelman et al (2019a) and is likely due to the rapid uptake of VFA by the gastrointestinal epithelium, limiting the value of fecal VFA content as a marker for hindgut VFA production (den Besten et al, 2013). However, it is possible to estimate the increase in VFA production in response to HFCG supplementation.…”
Section: Discussionmentioning
confidence: 52%
“…Postruminal infusion of calcium gluconate, a gluconic acid salt, has resulted in changes in fecal VFA profile and improved milk fat concentration in lactating dairy cows (Doelman et al, 2019b;McKnight et al, 2019). In a recent pilot study conducted by our group, a hydrogenated fat-embedded calcium gluconate (HFCG) compound fed to early-lactation dairy cows increased milk fat concentration and yield (Doelman et al, 2019a), in contrast to the null response observed when incorporating calcium gluconate directly into the diet without embedding it in fat (McKnight et al, 2019). This suggests that the hydrogenated fat matrix offers some degree of protection to the calcium gluconate from degradation in the rumen (Papas and Wu, 1997;Wu et al, 2012), and that following digestion of the fat matrix in the small intestine, the active ingredient is liberated and available for fermentation in the hindgut.…”
Section: Introductionmentioning
confidence: 99%